Badania soli rozpuszczalnych w wodzie za pomocą strefowej elektroforezy kapilarnej - Oberta, Wioleta; Łukaszewicz, Jadwiga (Acta Universitatis Nicolai Copernici Zabytkoznawstwo i Konserwatorstwo, 2016)
The water soluble salts influence on the monuments state of preservation remains a major and still open subject of conservation. The scientific conferences dedicated to the damages in buildings and sculptures under the influence of salts only confirm the importance of this subject. The stone monument state of preservation depends on the amount of the water soluble salts as well as on the salt type either. Thus the important scientific aim is a development of a precise but simple methods for quantitative and qualitative analysis of water soluble salts present in historical objects. The aim of this paper was a trial for evaluation of capillary zone electrophoresis application in conservation analysis of construction materials salinity. The research was conducted with the analysis of the salted samples of Pińczów limestone, Żerkowice sandstone and modern ceramic brick.